Attitude towards Learning Statistics and Factors Associated with it among University Students, Sarawak, Malaysia - Mizanur, Md Mizanur Rahman; Nik Hassan, Nik Noor Arba’iyah; Yusman, Nur Hanisah; Kam, Su Ling; Harith, Mohd Faiz (Trends in Undergraduate Research, 2024)
Statistics is a course required for most undergraduate university students. Statistical methods are often used in problem solving in various fields, including information, communication technology, medicine, etc. This study examined students’ attitudes towards learning statistics and its relationships with perceived academic performance, learning styles, and educational environment. This cross-sectional study at UNIMAS involved 610 undergraduate students. It used multistage cluster sampling and a questionnaire to assess attitudes towards statistics, learning styles, academic performance, and academic environment. Data were analysed using hierarchical multiple regression. The study examined attitudes toward learning statistics among 610 university students, predominantly female (65.9%) and in their second year (90.7%). Students reported moderate overall academic performance (M=3.49, SD=0.43), with the highest scores in group work. The perceived academic environment was generally positive, with sports facilities and empathy learning rated highest. The learning style preferences showed a strong inclination towards visual (84.1%) and sensing (73.3%) styles, with 87% having a mild overall preference. Attitudes towards statistics were slightly positive (M=4.57, SD=0.61), with the highest scores in the effort and interest domain. Hierarchical regression analysis revealed that group work (β=.159, p<.001), work productivity (β=.197, p<0.001), and the perceived academic environment (β=.139, p<.001) were significant predictors of attitudes towards statistics in multiple domains. Age and gender had minimal impact on attitudes towards statistics, except for a slight female preference in the value domain (β=.086, p<.05). The effort domain was positively influenced by group work (β=.207, p<.001), work productivity (β=.222, p<.001), and the academic environment (β=.252, p<.001). In contrast, the affective domain was negatively influenced by cognitive ability (β=-.115, p<.01) and impulse control (β=-.169, p<.001). These findings provide insight into the factors that affect student attitudes toward statistics, highlighting the importance of collaborative learning, productivity, and a supportive academic environment.